2018
DOI: 10.18314/jnb.v4i2.1249
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Fatty Acids Levels during Pregnancy and After Delivery in a Longitudinal Study

Abstract: Introduction: During pregnancy, several maternal metabolic adaptations occur. One of these adaptations is the significant changes in lipid metabolism which contribute to the nutrient balance of the fetal-placental unit, essential for fetal development and lactation.Methods: In this study, serum concentration of different fatty acids in healthy pregnant women and three months postpartum were determined by capillary gas chromatography and compared to healthy non-pregnant women and men. Differences between groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…We had previously determined the serum levels of NEFA by capillary gas chromatography-mass spectrometry (GC-MS) in a longitudinal cohort study of healthy pregnant women and three months postpartum and in non-pregnant women [ 39 ]. The results demonstrated that total levels of NEFA increased significantly during the mid-to-later pregnancy and similar results were reported by Herrera et al [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We had previously determined the serum levels of NEFA by capillary gas chromatography-mass spectrometry (GC-MS) in a longitudinal cohort study of healthy pregnant women and three months postpartum and in non-pregnant women [ 39 ]. The results demonstrated that total levels of NEFA increased significantly during the mid-to-later pregnancy and similar results were reported by Herrera et al [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that total levels of NEFA increased significantly during the mid-to-later pregnancy and similar results were reported by Herrera et al [ 29 ]. It is important to highlight that the pregnant women were randomly selected from the same original cohort of a NEFA study [ 39 ]. Additionally, previous studies have shown that circulating NEFA were significantly higher in women with preeclampsia than in normotensive pregnancies [ 37 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation